2006
DOI: 10.1063/1.2337407
|View full text |Cite
|
Sign up to set email alerts
|

On the validity of Avrami formalism in primary crystallization

Abstract: Articles you may be interested in Molecular dynamics of polymer crystallization revisited: Crystallization from the melt and the glass in longer polyethylene J. Chem. Phys. 139, 054903 (2013) Calorimetric data of primary crystallization is usually interpreted in the framework of the Kolmogorov ͓Dokl. Akad. Nauk SSSR 1, 355 ͑1937͔͒, Johnson and Mehl ͓Trans. AIME 135, 416 ͑1939͔͒, and Avrami ͓J. Chem. Phys. 7, 1103 ͑1939͒; 8, 212 ͑1940͒; 9, 177 ͑1941͔͒ ͑KJMA͒ theory. However, while the KJMA theory assumes random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 41 publications
1
59
0
Order By: Relevance
“…It is known that in polymorphic transformations, the competition between crystals are purely geometric and they stop growing due to direct hard impingement. 54 However, in the multicomponent solution studied here, soft impingement may be of primary importance due to the significant concentrating effect by the growth of the two competing iceballs (i.e., depletion of water molecules in the same region). In other words, the growth of two adjacent iceballs should be stopped by the dramatically elevated concentration of the solution layer commonly depleted by them, instead of the direct physical contact.…”
Section: Hard and Soft Impingementmentioning
confidence: 99%
“…It is known that in polymorphic transformations, the competition between crystals are purely geometric and they stop growing due to direct hard impingement. 54 However, in the multicomponent solution studied here, soft impingement may be of primary importance due to the significant concentrating effect by the growth of the two competing iceballs (i.e., depletion of water molecules in the same region). In other words, the growth of two adjacent iceballs should be stopped by the dramatically elevated concentration of the solution layer commonly depleted by them, instead of the direct physical contact.…”
Section: Hard and Soft Impingementmentioning
confidence: 99%
“…(Note that this is different from some other models, notably [13].) The present model focusses on the diffusion fields in the parent phase, and the fraction transformed is thus obtained from the concentrations in the parent phase, through Eq.…”
Section: A New Soft Impingement Modelmentioning
confidence: 99%
“…109-119 3 Some of the users of KW model have described this treatment of impingement as 'a simple response equation ' [12], i.e. it is an approximation for which the accuracy is as yet unproven and it has been suggested that the mean field approach underestimates impingement because it ignores a geometrical component to the impingement process [13]. The contribution of a geometrical component has been investigated in [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations